2022
DOI: 10.1080/20477724.2022.2035625
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency of RT-LAMP integrated CRISPR-Cas technique for COVID-19: A systematic review and meta-analysis

Abstract: To address the challenges associated with COVID-19 diagnosis, we need a faster, direct, and more versatile detection method for efficient epidemiological management of the COVID-19 pandemic. RT-qPCR (reverse transcription quantitative real-time Polymerase Chain Reaction) although the most popular diagnostic method suffers from a major drawback of equipment dependency and trained molecular biologists that limits rapid and large-scale screening, particularly in low resource regions. Reverse transcription loop-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We obtained an output of more than 7,000 articles as a result of a search using the keywords “RT-PCR diagnosis COVID-19”, of which almost 4,000 were published in 2021 alone. This result was compared with the findings of Bhatt et al ( 20 ) concerning papers related to RT-LAMP and CRISPR for SARS-CoV-2 diagnosis. Of these, we analyzed 10 articles on the RT-LAMP technique and 10 articles related to RT-LAMP-CRISPR-Cas technology, finding that only 1 applied the endonuclease Cas13 for SARS-CoV-2 diagnosis, but always on samples treated with an RNA extraction kit ( 21 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We obtained an output of more than 7,000 articles as a result of a search using the keywords “RT-PCR diagnosis COVID-19”, of which almost 4,000 were published in 2021 alone. This result was compared with the findings of Bhatt et al ( 20 ) concerning papers related to RT-LAMP and CRISPR for SARS-CoV-2 diagnosis. Of these, we analyzed 10 articles on the RT-LAMP technique and 10 articles related to RT-LAMP-CRISPR-Cas technology, finding that only 1 applied the endonuclease Cas13 for SARS-CoV-2 diagnosis, but always on samples treated with an RNA extraction kit ( 21 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 82%
“…Study of the state of the art revealed that greater efforts must be made to innovate in diagnostic methods; Bhatt et al ( 20 ) found 1,286 papers related to RT-LAMP and CRISPR for SARS-CoV-2 diagnosis (surprisingly, only 98 of these applied RT-LAMP integrated with CRISPR-Cas technology), in contrast with the 7,000 studies involving RT-PCR. This indicates that efforts should also be focused on developing more efficient RT-LAMP-CRISPR-Cas protocols without RNA purification, which would reduce the cost of the testing and also produce results faster.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained an output of more than 7000 articles as a result of "qPCR diagnosis COVID19" search, of almost 4000 in 2021 alone. This result was compared with findings of Bhatt A. et al [15] concerning papers related to RT-LAMP and CRISPR for SARS-CoV-2 diagnosis. Of these, we analyzed 10 articles on the RT-LAMP technique and 10 articles related to RT-LAMP-CRISPR-Cas technology, finding that only 1 applied the endonuclease Cas13 for SARS-CoV-2 diagnosis always on samples treated with an RNA extraction kit [35] (Table 3).…”
Section: Analysis Of the State Of The Artmentioning
confidence: 78%
“…Study of the state of the art revealed that greater efforts must be made to innovate in diagnostic methods, as Bhatt A. et al [15] found 1286 papers related to RT-LAMP and CRISPR for SARS-CoV-2 diagnosis, in contrast to the 7000 studies involving qPCR ( surprisingly only 98 of these applied RT-LAMP integrated with CRISPR-Cas technology). This indicates that efforts should also be focused on developing more efficient RT-LAMP-CRISPR-Cas protocols without purification of RNA, which would reduce the cost of the testing and also produce results faster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation